Human hope and the reign of God. Issue 1 (27th December 2021) - Jeanrond, Werner G.
Abstract: This article discusses the theological virtue of hope in relation to the Christian expectation of God's coming reign. Hope, as distinct from optimism and from all sorts of individualistic hopes, refers to God's gift of future. Hence, the tension between expecting God's coming reign, on the one hand, and the challenge of living constructively in the here and now, on the other hand, engages theological approaches to hope. It is argued that the divine gift of love, rather than faith, provides the main source of orientation for the Jewish and the Christian praxis of hope in this world. Faith is often understood in terms of assent to certain doctrinal definitions, while the other dimension of faith, God's offer of relationship, has moved to the background. Accepting love as guide to the Christian praxis of hope strengthens the relational nature of hope. No one can hope for herself or himself alone. The Gospels and the Pauline letters confirm the centrality of love for Christian discipleship. The article concludes with, first, a discussion of the contemporary challenge of migration; and, second, with a consideration of the connection between hope for personal fulfilment and hope for the future of the universe. Both examples point to a theology that is inspired by love and equipped to approach Christian discipleship in a spirit of hope.